Problem analysis functioning of technical systems "intelligent buildings" - Кульчицька, Т.І.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2006)
Tasks of the analysis of functioning of technical systems of an “intelligent building”. The basic tasks of the analysis of functioning of technical systems of an “intelligent building” and the concrete examples were considered.